Statistics in Social Sciences - UNGUREANU, Laura (Journal of Research in Educational Sciences; Vol 15 No 1 (2024): JRES, Volume XV, Issue 1(17), Summer 2024DO - 10.14505/jres.v15.1(17).06, 2024)
This work is the result of some research and documentation of the theoretical problems of statistics and its applications in the study of phenomena and processes in nature and society. Statistics has applications in the most diverse fields, such as: medicine, natural sciences, economics, politics, human behavior sciences, etc. Practically, in any field of human existence we witness operations of gathering, systematizing and interpreting information. That is why its role is very important. Therefore, this paper reviews some statistical methods that are used in social sciences. The focus is mainly on the applied aspect of the techniques and the author give insights about techniques that can be used to answer problems in the abovementioned areas of research. The article focuses on detailed explanations in the presentation of the consequences of the application of statistical procedures in the social sciences.